The dilemma of new psychoactive substances: A growing threat - Hawraa Sameer Sajwani (Elsevier, 2023)
New psychoactive substances (NPS) pose a major public threat and are a growing problem worldwide. They were designed to replace banned or controlled drugs while escaping quality control measures. Their chemical structure is constantly changed which imposes a major forensic challenge, and makes it difficult for law enforcement measures to track and ban them. Hence, they are called "legal highs" as they replicate illicit drugs whilst remaining legal.Low cost, easy accessibility and less legal liability are the main factors that contribute to the popularity of NPS among the public. This is particularly with the lack of knowledge of the health risks and harms associated with NPS not only amongst the public, but healthcare professionals as well, which further constitutes a challenge for preventative and treatment measures.Further medico-legal investigation, extensive laboratory and non-laboratory analyses, and advanced forensic measures are necessary to identify, schedule and control new psychoactive substances. Besides, additional efforts are required to educate the public and increase their awareness regarding NPS and their potential harms.